Synthesis and Biological Activity of Pyrazolo[4,3-c]heterocyclic Derivatives: A Mini Review - Wojcicka, Anna; Becan, Lilianna (Mini-Reviews in Organic Chemistry, 2015)
This review presents most of the literature data about synthesis and biological activity of pyrazolo[4,3-c]heterocyclic derivatives. Pyrazolo[4,3-c]heterocyclic derivatives show the antimicrobial, anti-inflammatory, antiviral, antitumor, analgesic and antiphlogistic activities, and effects on the nervous and immune system. The broad spectrum of biological activity of pyrazolo[4,3-c]heterocyclic derivatives is the main reason for the preparation of new compounds containing this scaffold.
Keywords: Biological activity